2015
DOI: 10.1017/s0022215115002091
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of type I tympanoplasty efficacy and histopathological changes to the tympanic membrane in dry and wet ear: a prospective study

Abstract: The success rate was not influenced by the presence of ear discharge at the time of surgery, and tympanic membrane vascularity did not influence graft uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 27 publications
3
27
1
Order By: Relevance
“…11 Shankar et al observed success rate of 88% in the dry ear group and 80% in the wet ear group (p=-0.324) and concluded that success rate is not influenced by the presence of ear discharge at the time of surgery. 12 The mean pre-operative pure tone audiometry (PTA) in group I was 30.57±7.80 dB while post-operative PTA was 20.68±8.22 dB with a mean hearing gain of 9.89 dB. The mean pre-operative PTA in group II was 35.21±5.98 dB while the post-operative PTA was 27.07±9.25 dB with a mean hearing gain of 8.12 dB.…”
Section: Discussionmentioning
confidence: 95%
“…11 Shankar et al observed success rate of 88% in the dry ear group and 80% in the wet ear group (p=-0.324) and concluded that success rate is not influenced by the presence of ear discharge at the time of surgery. 12 The mean pre-operative pure tone audiometry (PTA) in group I was 30.57±7.80 dB while post-operative PTA was 20.68±8.22 dB with a mean hearing gain of 9.89 dB. The mean pre-operative PTA in group II was 35.21±5.98 dB while the post-operative PTA was 27.07±9.25 dB with a mean hearing gain of 8.12 dB.…”
Section: Discussionmentioning
confidence: 95%
“…7,8 Histopathology of excised remnant TM in wet ears showed evidence of inflammatory cells and vascularization within stroma of fibroblasts while these were absent in dry ears which is similar to other studies who have postulated that vascularity and inflammation in cases of active COM has influence on graft uptake. 5,9 In this study the overall success rate in graft uptake following myringoplasty was 88.3%, with 86.7% in wet ears and 90% in dry ears. It was observed that there was no statistical significance (p value of 0.688>0.05) between the 2 groups in relation to graft uptake.…”
Section: Discussionmentioning
confidence: 51%
“…Other studies comparable to this study have shown that presence of ear discharge at the time of surgery has no significant bearing on the results of myringoplasty. 7,[9][10][11][12] A comparison of graft uptake of this study with other studies is given in Table 2. Mean hearing gain observed in wet and dry ears were 3.43 dB and 3.85 dB respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Many studies prove that wet or dry ears do not affect the success rate, but it should be mucoid and scanty. 10,11 Rashmi in his study on role of cortical mastoidectomy in type 1 tympanoplasty in 80 patients concluded that cortical mastoidectomy is not routinely necessary in all cases of CSOM but it is of definite help in sclerosed contracted mastoid with edematous polypoidal middle ear mucosa to remove aditus block, as performing mastoidectomy adds time, cost, and increased risk of postoperative complications. 12 In the present study we found out that the success rate in terms of graft uptake is 100% in cases where cortical mastoidectomy is done along with type 1 tympanoplasty, while it is 83.33% when tympanoplasty alone is done.…”
Section: Discussionmentioning
confidence: 99%